Developing scale to measure student's honesty characters on mathematics learning using subject scaling - Hidayati, Kana; Budiyono, Budiyono; Sugiman, Sugiman (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2018)
The purpose of this study is to develop a scale to measure honesty characters of students on mathematics learning using sucject scaling model. This development research is carried out in several steps namely: preparing initial scales, trials, and interpretation of trials result. The research is conducted on students of SMP N 5 Yogyakarta, SMP Muhammadiyah 2 Yogyakarta, and SMPIT Abu Bakar Yogyakarta. The first trial involves 688 students and the second trial involves 696 students. Content validity is obtained through expert judgment. The construct validity is determined by Lisrel's second order CFA. Reliability coefficients include Omega coefficients (Ï‰) and Alpha coefficients from Cronbach. Based on the results of this research, the scale to measure of student's honesty characters consists of 15 items that theoretically and empirically proved to be of good quality. The scale has good content validity supported by V Aiken index of 0.88-0.92. The scale has good construct validity. Reliability of the scale is also good supported by both the Omega coefficient of 0.86.